Geographic Internet domains: Challenges for the developing Domain Name System - Forrest, Heather Ann (Journal of Telecommunications and the Digital Economy, 2014)
Geographic names have posed challenges for Internet domain name policy makers since the earliest days of the Domain Name System (or ‘DNS’, as it is most commonly known). As the DNS develops with the addition of hundreds of new top-level domains and the challenges posed by geographic domains are addressed only on an ad hoc basis, DNS policy on these names reduces coherency, thus reducing confidence in the DNS and its controlling authority, the Internet Corporation for Assigned Names and Numbers (ICANN). The broad range of issues currently and foreseeably raised by the use of geographic names in the DNS means that all Internet stakeholders are affected, not simply those claiming rights or interests in such names. This article offers insight into why geographic domain names remain problematic more than two decades after these issues first arose, identifies trends in DNS policy respecting geographic names and highlights the impact on various Internet stakeholders of current policy and decisions.